Reassessing the Role of σ Holes in Noncovalent Interactions: It is Pauli Repulsion that Counts - Szczęśniak, Małgorzata M.; Chałasinski, Grzegorz (Frontiers in Chemistry, 2022)
A number of prototypical weak electron-donor-electron acceptor complexes is investigated by the Symmetry Adapted Perturbation Theory some of which belong to novel classes of weak bonds such as halogen and chalcogen bonds. Also included are complexes involving strong Lewis acids such as BeO and AuF. A literature view is to associate these novel bonds with variety of “holes”, σ, π, δ, or positive areas in their electrostatic potential maps. The presumption is that these positive areas of the electrostatic potential are indicative of the electrostatic nature of these noncovalent bonds. The electrostatic view extends to the explanations of the directionality of approaches between the subsystems forming these bonds. This work demonstrates that one common feature of these electrostatic potential “holes” is the local depletion of electron density of which the best detector is the first-order Pauli repulsion. The minimization of this repulsion determines the bond directionality and its relative angular rigidity. In relatively strong complexes of BeO with rare gases, where BeO shows a clear cavity in electron density – an ultimate “σ hole” - the electrostatic effect does not control the bending potential – the exchange repulsion does. In halogen bonds the halogen atom is nonspherical displaying a “σ hole” axially in its electrostatic potential, but in no case examined, from rare-gas acting as an electron donor to polar to anionic, is the electrostatic energy responsible for the directionality of the halogen bond and, in fact, it is not even maximized in the direction of the σ hole in N2-ClF and NH3-ClF. Yet in all the cases, the exchange repulsion is minimized in the direction of the σ hole. The minimized exchange repulsion associated with the subtle and less subtle depletions of the electron density occur on the nodal planes or on the intersections thereof in the highest occupied molecular orbitals of Lewis acids, provided that the systems are closed-shell. The role of nodal planes in covalent and coordinate covalent bonds is well recognized. This work points to their similarly equal importance in certain types of donor-acceptor noncovalent interactions.